1988
DOI: 10.1172/jci113340
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ca2+-dependent K+ channels in human B lymphocytes by anti-immunoglobulin.

Abstract: Many mammalian cell types exhibit Ca2l-dependent K+ channels, and activation of these channels by increasing intracellular calcium generally leads to a hyperpolarization of the plasma membrane. Their presence in B lymphocytes is as yet uncertain. Crosslinking Ig on the surface of B lymphocytes is known to increase the level of free cytoplasmic calcium ([Ca2l']). However, rather than hyperpolarization, a depolar- Ca2+1; response by omission of external Ca2" abolished the prolonged hyperpolarization. In fact, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Cells were added to the cuvette at a final concentration of 2 ϫ 10 6 cells/ml. Fluorescence was calibrated using ionomycin and Mn 2ϩ as described previously (15,16,22) using a dissociation constant of 250 nM (23).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were added to the cuvette at a final concentration of 2 ϫ 10 6 cells/ml. Fluorescence was calibrated using ionomycin and Mn 2ϩ as described previously (15,16,22) using a dissociation constant of 250 nM (23).…”
Section: Methodsmentioning
confidence: 99%
“…Although Ca 2+ entry across the plasma membrane would be expected to depolarize the cell, several studies of human T and B cells and mouse thymocytes have shown instead that membrane hyperpolarization accompanies the rise in [Ca2+]i (Tsien et al, 1982;Felber and Brand, 1983;Wilson and Chused, 1985;Tatham, O'Flynn, and Linch, 1986;MacDougall, Grinstein, and Gelfand, 1988; reviewed by Grinstein and Dixon, 1989). Preliminary fluorescent-indicator studies on individual cells indicate that oscillations in membrane potential accompany the [Ca2+]i oscillations in Jurkat T cells (Lewis, Grissmer, and Cahalan, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The first is a release of Ca" from intracellular stores mediated by an increase in intracellular inositol 1,4,5 trisphosphate (IP,); (Bijsterbosch et al, 1986;Monroe and Cambier, 1983). The second component is due to the entry of extracellular Ca2+ across the plasma membrane as evidenced by its dependence upon availability of extracellular Ca2+ (Bijsterbosch et al, 1986;MacDougall et al, 1988a). The net result of these mechanisms is a biphasic rise in [Ca"], with a transient peak due to release from stores subsiding to a lower sustained plateau phase maintained by influx of Ca2' from the extracellular medium.…”
mentioning
confidence: 99%